Could immigration prevent population decline? The demographic prospects of Germany revisited. - Weber, Hannes (Bundesinstitut für Bevölkerungsforschung, 2015)
Germany has a record of more than 40 years of below-replacement fertility and annual death surplus. Hence, it is commonly accepted that Germany's population will decline considerably in the coming decades. Recent increases in immigration may, however, challenge the official long-term demographic projections for Germany. This paper assesses the impact of a permanent higher-than-expected level of net immigration to Germany as in the past three years on the projections for population, age structure and ethnic makeup by mid-century. The paper adds a higher immigration variant to the Federal Statistical Office's latest Coordinated Population Projection and two variants of a (a) constant or (b) decreasing fertility rate among migrant women. It can be shown that with permanent net migration as high as in recent years (around 300,000 per annum), Germany's population would not significantly decrease in the coming decades but would rather remain at 80 million until 2050. On the other hand, the sharp rise in the old-age dependency ratio is only mildly weakened by increased immigration rates. This issue is therefore probably best addressed by other (or additional) means. The increase in retirees will level off after 2035 in any case. The ethnic makeup of society would be affected to a greater degree than its age composition: The share of first- and second-generation immigrants among the total population is projected to rise to about 35 percent in this scenario (and to above 40 percent if the third generation is also counted).
Keywords: Bevölkerungsentwicklung; Einwanderung; Bevölkerungsstruktur; Zuwanderung; Demographischer Wandel; Ethnische Minderheit; Bevölkerungsgruppe; Migrationshintergrund; Bevölkerungsvorausberechnung; Einwanderungspolitik; Bevölkerungsrückgang